Spatially Resolved Metabolomics and Network Pharmacology Reveal Extract D Nephrotoxicity Mechanisms in Pleuropterus multiflorus Thunb. - Haiyan Jiang; Ying Wang; Xiaoyan Duan; Shushu Guo; Xiaoyu Fan; Tianyu Zhou; Jie Li; Jiuming He; Jianbo Yang; Hongtao Jin (Toxics)
As a traditional Chinese medicine, the adverse hepatotoxicity effects of Pleuropterus multiflorus (Thunb.) Nakai (PM) have been documented. However, nephrotoxicity has been neglected as studies related to kidney toxicity mechanisms are limited. Our previous research reported that extract D [95% ethanol (EtOH) elution, PM-D] in a 70% EtOH PM extract showed more significant hepatotoxicity than other extracts. In the current study, PM-D was continuously administered to mice for 7 days at a dose of 2 g/kg (equivalent to a human dose of 219.8 mg/kg), which increased renal biochemical indexes and caused pathological kidney injury, suggesting renal toxicity. Therefore, network pharmacology and spatially resolved metabolomics were conducted to explore nephrotoxicity mechanisms underpinning PM-D. Network pharmacology indicated that BCL2, HSP90, ESR1, and CTNNB1 genes were core targets, while the phosphoinositide 3-kinase (PI3K)/protein kinase B(AKT)/signaling pathway was significantly enriched. Spatially resolved metabolomics indicated heterogeneous metabolite distribution in the kidney, further indicating that PM-D nephrotoxic metabolic pathways were enriched for α-linolenic acid and linoleic acid metabolism, pyrimidine metabolism, carnitine synthesis, and branched-chain fatty acid oxidation. Our comprehensive analyses highlighted that nephrotoxicity mechanisms were related to oxidative stress and apoptosis induced by disordered energy metabolism, lipid metabolism issues, and imbalanced nucleotide metabolism, which provide a platform for further research into PM nephrotoxicity mechanisms.